PENGARUH UPAH, BELANJA DAERAH, FILANTROPI ISLAM, PENDIDIKAN, PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI INDONESIA TAHUN 2011-2022 - Muhammad Amin Azis; Taosige Wau (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Poverty is still a big problem for third world countries, high levels of poverty can become social pathology. This research aims to determine the influence of wages, regional spending, Islamic philanthropy, education, economic growth and population on poverty in Indonesia. This research uses a panel data regression analysis method for the years 2011-2022. The results of this research show that simultaneously all variables have a significant influence on poverty in Indonesia in 2011-2022 amounting to 99.1% and 0.9 is influenced by other variables outside this research. partially, the variables wages, regional expenditure and population have a significant negative effect on poverty in Indonesia in 2011-2022. The variables Islamic philanthropy, education and economic growth have no effect on poverty in Indonesia